Assessment of Teaching Effectiveness, Digital Literacy, and Feedback on Student Assignments using ChatGPT - Lalu Sucipto; Habibi Ratu Perwira Negara (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2023)
Abstract:  This study aims to evaluate the Teaching Effectiveness, Digital Literacy, and Feedback on Student Assignments using ChatGPT in the context of mathematics education in higher education settings. A quantitative method was employed with a sample of 29 students from various semesters. The research instrument utilized was a questionnaire using the Likert Scale, comprising 10 items to measure Teaching Effectiveness, 9 items for Digital Literacy, and 7 items for Feedback on Student Assignments. Descriptive statistical analysis revealed average scores of 73.586 for Teaching Effectiveness, 73.180 for Digital Literacy, and 73.990 for Feedback on Student Assignments. These findings provide deeper insights into students' perceptions of ChatGPT usage in mathematics education and offer insights into the distribution and characteristics of values obtained from respondents. The implications of this research can be utilized for the development and enhancement of ChatGPT's utilization in providing effective feedback on student assignments in academic environments.